Subcutaneous trastuzumab (Herceptin) versus intravenous trastuzumab for the treatment of patients with HER2-positive breast cancer: A time, motion and cost assessment study in a lean operating day care oncology unit. (February 2018) - Tjalma, Wiebren A.A.; Van den Mooter, Tom; Mertens, Tim; Bastiaens, Valerie; Huizing, Manon T.; Papadimitriou, Konstantinos
Abstract: Objective: The subcutaneous (SC) formulation of trastuzumab represents an alternative to the intravenous (IV) infusion in the treatment of patients with HER2-positive metastatic and early breast cancer. We compared the two formulations in terms of time and cost differential. Study desing: We conducted a time, motion and cost assessment study in a lean operating day care oncology unit to determine and compare the time and costs of trastuzumab SC versus IV administration in patients with HER2-positive breast cancer. Outcomes were the mean costs and the mean dedicated time of the health care professional (HCP) and patient chair time. Direct observation methodology was applied to collect data and statistical analysis was performed. Results: The total preparation and administration time for trastuzumab IV was 4.07 times longer than the total time required for the trastuzumab SC administration. The total patient time spent in the day care oncology unit (in minutes) was 71% shorter with using SC administration. IV administration costs € 50.4 ($54, 89) more in HCP time and consumable supplies and €162.53 ($177.00) of drug wastage. SC administration was associated with a total time saving of 53.7 min for the HCPs and 122.5 min for the patients. The administration of trastuzumab SC was translated in a cost saving of €212.93 ($231.73) per patient episode compared to trastuzumab IV, which could lead to a total potential saving of €3, 832.74 ($4, 171.06) over a full course of treatment (18 cycles) Conclusion: SC administration of trastuzumab was associated with a substantial reduction in active HCP time, patient chair time, unit time, and overall cost. These time and cost could be used to increase capacity within existing resources in a lean operating day dare oncology unit.